Silenced and privileged voices in media discourses: Climate change and social capital - Maha Bashri; Sameera T. Ahmed (PLoS ONE, 2026)
Media representations and narratives around climate change are often dominated by certain voices whilst others are excluded or marginalized. This study investigates media portrayal of climate change around Glasgow’s COP26, focusing on the prominence or exclusion of certain voices. Analyzing US and UK newspaper coverage, it identifies variances in representation, with Indigenous and minority voices marginalized in favor of political, scientific, and activist perspectives from the Global North. Through content analysis, the research explores how power, access, and frames shape media narratives on climate change, underscoring the need for more inclusive discussions.